2015
DOI: 10.1007/s00384-015-2230-x
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation narrow band imaging system for colonic polyp detection: a prospective multicenter randomized trial

Abstract: Although WA colonoscopy did not improve the polyp detection, next-generation NBI colonoscopy represents a significant improvement in the detection of colonic polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 29 publications
4
55
0
Order By: Relevance
“…The evaluation was performed by four endoscopists who had not viewed any of these videos before this study. Of the four endoscopists, two were classified as non-experts (had performed < 5000 colonoscopies and 10 – 30 withdrawing colonoscopies with BLI-bright and LCI) and two were classified as experts (had performed ≥ 5000 colonoscopies and 300 withdrawing colonoscopies with BLI-bright and LCI) according to a previous report 9 . All of the videos were viewed in a randomized order.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation was performed by four endoscopists who had not viewed any of these videos before this study. Of the four endoscopists, two were classified as non-experts (had performed < 5000 colonoscopies and 10 – 30 withdrawing colonoscopies with BLI-bright and LCI) and two were classified as experts (had performed ≥ 5000 colonoscopies and 300 withdrawing colonoscopies with BLI-bright and LCI) according to a previous report 9 . All of the videos were viewed in a randomized order.…”
Section: Methodsmentioning
confidence: 99%
“…However, the polyp miss rate under white light (WL) observation was reported to be 20 – 25 % 5 . Therefore, narrow-band imaging (NBI; Olympus Medical Co., Tokyo, Japan), flexible spectral imaging color enhancement (FICE; Fujifilm Co., Tokyo, Japan), and chromoendoscopy were investigated to determine whether they could improve the polyp detection rate; however, most of them failed 6 7 8 9 10 11 . …”
Section: Introductionmentioning
confidence: 99%
“…Previously, we clarified that the new generation of NBI by the LUCERA ELITE system improved better polyp visibility score than WLI [17]. A multicenter study showed that new generation NBI (LUCERA ELITE system) improved polyp detection rate [7]. Additionally, we clarified that BLI-bright in laser endoscopic system yielded a better polyp visibility score than WLI [9].…”
Section: Discussionmentioning
confidence: 99%
“…The possible reasons for missing these lesions include poor visualization of the back of the folds and inner curve of the flexures [5], as well as insufficient physician endoscopic technique [6, 7]. Several reports of high-definition, wide-angle colonoscopy have provided significantly improved polyp detection rates compared with those achieved with SC [8, 9]. …”
Section: Introductionmentioning
confidence: 99%